2937. A triangle construction - T. E. Easterfield (The Mathematical Gazette, 1961)
Introduction Skeletal muscle is an essential tissue for insulin-stimulated glucose uptake. Myokines are proteins, peptides, and other metabolites that are released by muscles and exhibit metabolic functions. Decorin, apelin and TRIM72 are myokines with connection to insulin action. The aim of this paper was to study the expression of these selected myokines in skeletal muscle in relation to insulin sensitivity in individuals without overt metabolic disturbances. Methods Thirty healthy young male volunteers with normal glucose tolerance, 14 normal-weight, 8 with overweight and 8 with obesity, were included in the study population. The vastus lateralis muscle biopsies were performed. Insulin sensitivity (IS) was tested with hyperinsulinemic-euglycemic clamp. Muscle tissue mRNA expresion was assessed via quantitative PCR. Results Group consisting of individuals with obesity had lower insulin sensitivity compared to those with normal weight and overweight. Apelin expression was significantly higher in the obese group compared to the normal-weight and overweight groups. All myokines' expressions correlated with insulin sensitivity, decorin - positively, apelin and TRIM72 - negatively. Only apelin was correlated positively with BMI. Apelin was correlated with insulin sensitivity independently of BMI, decorin was also correlated with insulin sensitivity independently of BMI. Conclusion Apelin, decorin and TRIM72 are correlated with insulin sensitivity and decorin and apelin have BMI-independent associations. This suggests that these molecules can be linked to metabolic health.